HABITAT MIKRO TABAT BARITO (Ficus Deltoidea Jack) DI KELURAHAN JAMBU KECAMATAN TEWEH BARU DAN DESA PENDREH KECAMATAN TEWEH TENGAH KABUPATEN BARITO UTARA PROVINSI KALIMANTAN TENGAH - Nisa, Fitriatun; Asy'ari, Mufidah; Fithria, Abdi; Hatta, Gusti Muhammad (Universitas Lambung Mangkurat, 2024)
The high diversity of plants in Indonesia provides many benefits for the community, one of which is the use of plants as traditional medicines so that the prospects for rnedicinal plant agro-industry in lndonesia are very large. The exploitation of forests and land for plantation and rnining activities in North Barito District is currently threatening the existence of the tabat barito as one of the plants that live in the forest. The objectives of this study were to identify the microhabitat characteristics of barito tabat in its native habitat. Tabat barito was found to live attached to 2 types of host trees, namely kuyum bakei trees (Elaeocarpus sp. ) and kacuhui trees (Shorea sp.). These two types of host plants have similarities in terms of habitat where they grow and similar trunk characteristics, namely thick, grooved bark, easily cracked and porous and can peel. The microclimatic conditions measured were elevation 29 - 64, ternperature range 32 - 33.1